Investigation on the Creep Failure Mechanism of Sandy Mudstone Based on Micromesoscopic Mechanics. (6th August 2021) - Shi, Xinshuai; Jing, Hongwen; Chen, Weiqiang; Gao, Yuan; Zhao, Zhenlong
Abstract : In this paper, scanning electron microscope (SEM) tests and 3D scanning technologies were adopted to investigate the creep failure mechanism of sandy mudstone from a micromesoscopic view. The SEM test results showed that the fracture surface micromorphology of the specimens that suffered creep loading was more fractured and rougher. It was also found by the fractal analysis of the SEM microscopic images that the fractal dimensions of the creep failure specimens were larger than those of the uniaxial compression failure, indicating that the creep damage increased the irregularity and a larger degree of roughness fluctuation. The 3D scanning technologies combining with the 3D reconstruction methods proved that the crack expansion path of crept specimens was more complicated, showing a more prominent asperity height and slope angle. Finally, a mesostrain dilating microelement model of the sandy mudstone specimen's fracture surface was proposed to prove that the dilatancy effect would be more pronounced in the creep process.